Anchoring nickel nanoparticles on three-dimensionally macro-/mesoporous titanium dioxide with a carbon layer from polydopamine using polymethylmethacrylate microspheres as sacrificial templates. (12th December 2018) - Zheng, Jing; Zhang, Min; Miao, Teng; Yang, Jingxia; Xu, Jingli; Alharbi, Njud S.; Wakeel, Muhammad
Abstract : Herein, three dimensional (3D) macro-/mesoporous TiO2 @C–Ni composites have been successfully fabricated, which endowed the composites with enhanced performance in catalysis and protein adsorption. Abstract : The performance in adsorption and catalysis efficiency are closely dependent on the morphology and structure of the catalysts and adsorbents. Herein, three dimensional (3D) macro-/mesoporous TiO2 @C–Ni composites were successfully fabricated using polymethylmethacrylate (PMMA) as a sacrificial template. Notably, the inorganic interlayer of TiO2 or SiO2 played an essential role in generating such 3D macro-/mesoporous TiO2 (SiO2 )@C–Ni composites. In the absence of TiO2 or SiO2, aggregated C–Ni composites were obtained instead. Owing to the well-defined 3D macro-/mesoporous structures as well as high coverage of Ni nanoparticles (NPs), the TiO2 @C–Ni composites obtained at 500 °C in a N2 atmosphere exhibited excellent performance in catalysis and protein adsorption. Moreover, the morphology of the 3D TiO2 @C–Ni composites was greatly influenced by changing other different carbonization temperatures (700, 900 °C). Interestingly, when PMMA@TiO2 @PDA–Ni 2+ was annealed at 900 °C, all of the generated carbon nanotubes as well as the TiO2 interlayer were weaved together into a continuous 3D network, which will endow this kind of material with enhanced properties and excellent performance in energy storage fields.